What's wrong with my gallbladder? understanding laparoscopic cholecystectomy - Loh, Wei-Liang (World Scientific Publishing Co. Pte. Ltd., 2016)
"The minimally invasive surgical removal of the gallbladder, known as laparoscopic cholecystectomy, is one of the most commonly performed operations today. Yet, patients do not have a full understanding of the procedure and often, search the internet for answers. This concise book aims to bridge the knowledge gap between surgeons and patients by explaining the various aspects of the procedure in detail, educating patients and their relatives who are eager to understand more about the procedure and condition. Readers will be brought through the basics of gallbladder anatomy and physiology, operative procedure and post-operative care. All procedures are richly illustrated in colour to import greater understanding and a more immersive experience to readers. With chapters on operative procedures and challenging scenarios faced, medical undergraduates and junior doctors will also find this book useful as it provides in-depth practical knowledge that will be invaluable to them as they embark on their own training and practice."--